Ethnophysics Literature Study of “Tarik Tambang” and “Balap Karung” in the Application of Newton's Law Physics Concepts - Simangunsong, Rufasa Mutia Salwa; Aini, Hikmah; Sari, Lindya; Silalahi, Jihan Syifa; Harahap, Nadia Ulfah; Sigiro, Welki Bahri; Panggabean, Deo Demonta (Universitas Pendidikan Mandalika, 2025)
This study aims to examine the physics concepts embedded in the traditional Indonesian games Tarik Tambang (Tug of War) and Balap Karung (Sack Race) through the application of Newton’s Laws. Conducted within the framework of ethnophysics, the research seeks to bridge scientific principles with local wisdom to foster contextual and engaging physics learning for students. A qualitative approach utilizing literature review was employed, analyzing various scholarly sources related to traditional games and their underlying physical principles. The findings reveal that Tarik Tambang illustrates Newton’s Second Law of Motion and the role of static friction. The game demonstrates how the acceleration of the opposing team is determined by the net pulling force and total system mass, while static friction is essential for maintaining player balance and traction. Additionally, strategies such as placing heavier players at the back enhance force generation and overall team performance. In Balap Karung, Newton’s Third Law and momentum significantly influence participants’ movements. The forward propulsion results from the backward action force exerted by the feet, which is met with an equal and opposite ground reaction force. Momentum affects the stability and speed of the jump, and friction between the sack and ground determines the efficiency of motion. This research highlights the pedagogical potential of traditional games in physics education. By contextualizing Newtonian mechanics through culturally familiar activities, students can develop a more concrete understanding of physical laws. The study recommends incorporating such games into instructional strategies to promote meaningful and culturally responsive science learning.